New Testament Paradigm of the Unity of Christians - Miško Horvatek (Kairos (English Ed.), 2008)
The intention of this article is to describe: first, the New Testament paradigm of unity, second, the New Testament nature of unity, and third, the New Testament teaching concerning the responsibility of leaders to maintain unity. Viewed from a New Testament standpoint, the first section discusses the notion of unity: unity of the believers with the Lord, unity of the believers within Christ’s body, unity in diversity within Christ’s Church, then about unity in the Spirit, and finally about the unity toward which we are to incline. The second section deals with the New Testament nature of the unity of the Church, which is a spiritual unity, though it also must be practical. The third section emphasizes the New Testament teaching concerning pastoral responsibility in maintaining and protecting the fellowship. Application of Peter’s, John’s and Paul’s exhortations is a secure way toward the upkeep and maintenance of true biblical unity and practical spiritual fellowship within Christ’s body.